2016
DOI: 10.1126/science.aah5243
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule optomechanics in “picocavities”

Abstract: Coinage metal nanostructures support localised surface plasmons, which confine optical fields much tighter than their wavelength (1). This extreme enhancement enables vibrational spectroscopy within small volumes, even down to single molecules (2,3). For many years lateral resolution was believed to be 10 nm (4), however recent experiments resolve the atomic structure of single molecules using tipenhanced Raman spectroscopy (3) and directly sequence RNA strands (5). Atomistic simulations also suggest plasmonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
890
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 735 publications
(918 citation statements)
references
References 34 publications
23
890
3
2
Order By: Relevance
“…The nature of chemical bonds as quantum vibrational oscillators can now be very effectively manipulated by trapping light tightly enough around molecules [8]. Analogous optomechanical systems use macroscopic vibrational modes such as cantilevers [9,10], beams [11], or pillars [12][13][14][15] coupled to highfinesse optical cavities in order to demonstrate a variety of effects such as cooling to the quantum vibrational ground state [16], parametric oscillation [17], and supercontinuum comb generation [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nature of chemical bonds as quantum vibrational oscillators can now be very effectively manipulated by trapping light tightly enough around molecules [8]. Analogous optomechanical systems use macroscopic vibrational modes such as cantilevers [9,10], beams [11], or pillars [12][13][14][15] coupled to highfinesse optical cavities in order to demonstrate a variety of effects such as cooling to the quantum vibrational ground state [16], parametric oscillation [17], and supercontinuum comb generation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Analogous optomechanical systems use macroscopic vibrational modes such as cantilevers [9,10], beams [11], or pillars [12][13][14][15] coupled to highfinesse optical cavities in order to demonstrate a variety of effects such as cooling to the quantum vibrational ground state [16], parametric oscillation [17], and supercontinuum comb generation [18]. Recent theory [19,20] and experiments [8,21] have shown that this same optomechanical Hamiltonian describes vibrating molecular bonds in nanocavities, but with single-photon coupling coefficients ℏg 0 ∼ 10-100 meV, a millionfold larger than for macroscopic resonators. Here, we explore how this coupling can be used to elicit stimulated phonon scattering within vibrating bonds, leading toward phonon lasing or "phasing," observed previously in microfabricated mechanical oscillators [22][23][24], and we suggest how such mechanical resonances can lead to chemical reactions [ Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it has been recently shown that sub-nanometric inhomogeneities in field-enhancement patterns in plasmonic gaps [24][25][26] can be described, at least qualitatively, through classical optics calculations. On the other hand, the physical mechanisms behind the failure of classical predictions for the LSPR frequencies in compact nanoparticles (with sizes in the ∼ 1-3 nm range) are well understood.…”
mentioning
confidence: 99%
“…Duan and Luo have proposed involvement of nonlinear optical processes [47]. Creation of an "atomic-scale hot spot" has also been proposed [48]. In addition, multiple elastic scattering of light between molecular dipoles adsorbed on the surface has been proposed to explain the improved signal intensity and TERS spatial resolution [49].…”
Section: Understanding Tersmentioning
confidence: 99%